Fasting or caloric restriction for Healthy Aging - Anton, Stephen; Leeuwenburgh, Christiaan (Experimental gerontology, 2013)
Aging is associated with a host of biological changes that contribute to a progressive decline in cognitive and physical function, ultimately leading to a loss of independence, and increased risk of mortality. To date, prolonged caloric restriction (i.e., a reduction in caloric intake without malnutrition) is the only non-genetic intervention that has consistently been found to extend both mean and maximal life span across a variety of species. Most individuals have difficulty sustaining prolonged caloric restriction, which has led to a search for alternative approaches that can produce similar to benefits as caloric restriction. A growing body of evidence indicates that fasting periods and intermittent fasting regimens in particular can trigger similar biological pathways as caloric restriction. For this reason, there is increasing scientific interest in further exploring the biological and metabolic effects of intermittent fasting periods, as well as whether long-term compliance may be improved by this type of dietary approach. This special will highlight the latest scientific findings related to the effects of both caloric restriction and intermittent fasting across various species including yeast, fruit flies, worms, rodents, primates, and humans. A specific emphasis is placed on translational research with findings from basic bench to bedside reviewed and practical clinical implications discussed.